"Feeling Anxious about Catching COVID": Facilitators and Barriers of Sleep Health among Young Adults with Type 1 Diabetes. Issue 3 (4th May 2022) - Griggs, Stephanie; Harper, Alison; Pignatiello, Grant; Hickman, Ronald L.
ABSTRACT: Background: The COVID-19 pandemic has imposed pervasive stress and significant disruptions in sleep health in young adults. The purpose of this study was to describe the perceived facilitators and barriers of sleep health among young adults with type 1 diabetes during the COVID-19 pandemic. Participants: Thirty-two young adults with T1D (87.5% female; mean age = 21.5, SD = 2.0) participated in an online survey between January and July 2021. Young adults between the ages of 18–25 years with T1D for at least 6 months were eligible to participate, while those who had a previous OSA diagnosis, were currently pregnant, or worked the night shift were not eligible to participate. Methods: A qualitative descriptive approach was used to explore the perceived facilitators and barriers to sleep among a convenience sample. Qualitative content was analyzed and coded for themes using qualitative content analysis. Responses were coded using an in vivo approach. Results: Young adults with T1D identified changes in facilitators and barriers of sufficient sleep from before the COVID-19 pandemic to during the pandemic. Three overarching barriers and facilitators were identified: (1) general, (2) diabetes-specific, and (3) COVID-19 specific. Conclusions: Our findings can inform future educational and cognitive-behavioral interventions to promote sleep health in young adults with T1D and other complex chronic conditions. When designing sleep-promoting interventions for young adults with T1D in the COVID-19 pandemic and post-pandemic, researchers should consider T1D as well as COVID-specific barriers and facilitators.